The Role of Radiology, Radiological Protection, and Medical Physics in the Diagnosis and Management of Cancer - Bima, Tahani Kamal; Slim , Shamma Mohammed; Alyahyawi, Alaa Arif; Alghamdi, Majed Jamman Awwadh; Alghamdi, Adil Saaban; AlhamziI, Eyad Dakhil Allah; Alqarni, Fahad Ali; Alshammari, Salman Abdullah Swailem; Alrashdi, Hamed Khalifa Hamed; Alshammary, ‏Falah Nazal Fahied (Journal of Ecohumanism, 2024)
Introduction: Cancer is still one of the leading causes of morbidity and mortality throughout the world, and its incidence grows every year due to the expansion of ageing populations and changing environments. This makes diagnosis and management paramount in preventing or else minimizing its effects, while the combination of radiology, radiological protection, and medical physics in oncology care has greatly advanced. These fields have enhanced the early diagnosis, accurate staging, management and therapy control hence improving the prognosis of patients. Aim of work: To explore and analyze the interconnected roles of radiology, radiological protection, and medical physics in the diagnosis and management of cancer. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Role, Radiology, Radiological Protection, Medical Physics, Diagnosis, Management, and Cancer. The search was restricted to publications from 2016 to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: Radiology, radiological protection and medical physics are disciplines that constitute essential contributions for the diagnosis and treatment of cancer, providing new opportunities to face challenges. Radiology is the picture-making establishment while radiological protection is the guarantee for radiation safety, and medical physics is the intermediary between technology and medicine. Altogether, they facilitate well-controlled accurate cancer interventions and reemphasize the significance of integrated melanoma treatment constituting rigorous development. These disciplines will undoubtedly propel the advances as oncology develops so that incident detection and treatment is optimized and patient survivability is enhanced.